Occurrence and environmental fate of pharmaceuticals, personal care products and illicit drugs (PPCPIDs) in tropical ecosystems - Maranho, Luciane Alves; dos Santos, Dayana Moscardi; da Fonseca, Tainá Gárcia; dos Santos Barbosa Ortega, Andressa [UNESP]; da Silva Sousa, Lorena; Pusceddu, Fabio Hermes; Cortez, Fernando Sanzi; Barbosa Moreno, Beatriz; Costa Melo, Luiza [UNESP]; Nobre, Caio Rodrigues [UNESP]; Fontes, Mayana Karoline [UNESP]; Cesar, Augusto; et al. (Elsevier, 2021)
The inefficient or lack of treatment of wastewaters in developing countries can lead to increased input of pharmaceuticals, personal care products, and illicit drugs (PPCPIDs) into the environment. Current scenarios, as acidification of oceans and pollution by microplastics should increase the impacts of PPCPIDs. This chapter reviews the sources, concentrations, and potential impacts of PPCPIDs in tropical coastal environments to support risk assessments and to identify key knowledge gaps as priorities for future research.
Keywords: Coastal environments; Developing countries; Emerging contaminants; Nontarget organisms; Sewage